2019
DOI: 10.3390/su11071945
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Comparison of Water Quality Treatment in a Bioretention Cell 16 Years Following Initial Analysis

Abstract: One of the most popular stormwater practices in (sub-)urban North Carolina is bioretention. While bioretention has been researched intensively to determine the most efficient designs, few long-term studies have attempted to assess the performance of older bioretention. However, previous research and design guidance for bioretention has predicted long-term water quality treatment. This study compared discharged concentrations and loads of nitrogen and phosphorus from a bioretention cell (1) post-construction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…High nitrate removal rates are observed with soil media containing higher organic matter [116]. In fact, the use of a carbon source has been proven to be successful in various systems [110,111,117,118], however, reducing the amount of carbon source additives in the soil media is also recommended to avoid N leaching [5,119], because excessive use of carbon source additives can sometimes be the source of nutrients leaching [35,101].…”
Section: Design Features That Enhanced Nitrogen Removalmentioning
confidence: 99%
“…High nitrate removal rates are observed with soil media containing higher organic matter [116]. In fact, the use of a carbon source has been proven to be successful in various systems [110,111,117,118], however, reducing the amount of carbon source additives in the soil media is also recommended to avoid N leaching [5,119], because excessive use of carbon source additives can sometimes be the source of nutrients leaching [35,101].…”
Section: Design Features That Enhanced Nitrogen Removalmentioning
confidence: 99%
“…The TN load reductions increased from 40% to 72%, while TP load reductions increased from 65% to 79%. The top 20 cm of the bioretention media was close to phosphorous saturation (Johnson & Hunt, 2019). Carbon stocks measured in 25 bioretention cells in Australia showed that the most C accumulation occurred in the upper 20 cm of the system, with around 32% of all C in the system limited to the top 5 cm (Kavehei, Jenkins, Lemckert, & Adame, 2019).…”
Section: Field Laboratory and Modeling Performance Studies: Field Smentioning
confidence: 99%
“…Bioretention is a small depressed area consisting of engineered soil media and vegetation which allows stormwater runoff to percolate slowly through (Liu et al 2014). Bioretention has been shown to reduce significant amounts of surface water runoff (Hatt et al 2009;Davis et al 2012;Khan et al 2012;Winston et al 2016;Johnson & Hunt 2019), which improves water quality largely by reducing the load of contaminants into surface water bodies. Bioretention has many co-benefits beyond stormwater management such as carbon sequestration in plants and trees (Kavehei et al 2018), evaporative and shading cooling to reduce urban heat island effect ( Jamei & Tapper 2019), and improved quality of life and land values (Foster et al 2011).…”
Section: Introductionmentioning
confidence: 99%